2012
DOI: 10.4103/0970-9290.111254
|View full text |Cite
|
Sign up to set email alerts
|

Salivary flow and dental caries in Brazilian youth with type 1 diabetes mellitus

Abstract: The lower salivary flow rate in diabetics could have been related to their higher GBI. The higher GBI in the diabetics is a matter of concern in the diabetics and is a sign for higher chances of developing periodontal problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 0 publications
2
24
1
7
Order By: Relevance
“…Studies by Sadia Iqbal et al, Jawed et al, Akapata et al, have reported increased incidence of dental caries among diabetes mellitus patients [12][13][14]. In contrast, studies by Collin HL et al, and Alves C et al, reported that no differences were found in the DMFT score among diabetics and non-diabetics [15,16].…”
Section: Discussionmentioning
confidence: 67%
“…Studies by Sadia Iqbal et al, Jawed et al, Akapata et al, have reported increased incidence of dental caries among diabetes mellitus patients [12][13][14]. In contrast, studies by Collin HL et al, and Alves C et al, reported that no differences were found in the DMFT score among diabetics and non-diabetics [15,16].…”
Section: Discussionmentioning
confidence: 67%
“…Istnieją doniesienia o wzroście zapadalności na próchnicę u chorych na cukrzycę [15]. Część autorów nie stwierdza znaczących różnic w zapadalności na tę chorobę u pacjentów z cukrzycą, ale podkreśla jej znacznie większe ryzyko [15][16][17]. U właściwie leczonych chorych na cukrzycę na ogół stwierdza się podatność na próch-nicę zbliżoną do osób zdrowych (nieznacznie wyższe wartości w grupie chorych) [18].…”
Section: Tabela 2 Uzębienie Stałe -Intensywność Próchnicy I Efektywnunclassified
“…Este é um estudo pioneiro em Portugal, considerando que a população em estudo é constituída por Relativamente à eventual relação entre a DM1 e um risco aumentado de desenvolver cárie dentária, os estudos disponíveis apresentam resultados contraditórios quando comparados doentes diabéticos e doentes não diabéticos. Alguns autores constataram um aumento deste risco [22][23][24] (traduzido por uma maior prevalência), e outros ou não verificaram qualquer relação significativa 25,26 ou relataram, inclusivamente, uma diminuição do risco. [19][20][21] O International Caries Detection and Assessment System (ICDAS-II) foi desenvolvido tendo por base sistemas de diagnóstico previamente aplicados, na tentativa de solucionar a disparidade entre os mesmos.…”
Section: Discussionunclassified
“…27,[40][41][42] Porém, esta relação é controversa e outros autores referem que os doentes diabéticos têm, tendencialmente, mais placa bacteriana. 21,26,43 Relativamente às complicações orais da DM e, nomeadamente, à cárie dentária, embora o GDM1 apresente valores ligeiramente superiores ao GC, no que se refere a dentes cariados, perdidos e restaurados não observámos diferenças estatisticamente significativas entre eles. Este resultado está de acordo com alguns estudos já publicados, que não registaram diferenças na prevalência de cárie em diabéticos tipo 1 quando comparados com doentes não diabéticos.…”
Section: Discussionunclassified
See 1 more Smart Citation